Implementasi Kebijakan Full Day School Di SDN 3 Blimbing Kota Malang - Ubaidillah, Ubaidillah; In’am, Akhsanul (Program Studi Magister Pedagogi, 2018)
Abstract: This study aims to describe 1) the implementation of full-day school policies conducted at SDN 3 Blimbing; 2) problems faced by SDN 3 Blimbing in implementing full-day school; 3) the solutions made in solving the problem of implementing full-day school policies in SDN 3 Blimbing. The research method used is a qualitative approach with the type of research is descriptive. Data obtained through interviews, observation, and study documentation. The results of this study indicate that the implementation of the full-day school policy has been based on the Character Strengthening Policy made by the Ministry of Education of the Republic of Indonesia. The aim of a full-day school implemented at SDN 3 Blimbing Malang is that students have the character set by the Ministry of Education of the Republic of Indonesia. Problems that arise during the implementation of full-day school among other facilities and infrastructures that are inadequate, the adaptation of teachers, employees, and students that require a relatively long time, concerns parents of students towards their children who sit in grades 1 and 2 and adjusting school schedules and student activities outside of school that have been previously scheduled. The solution carried out by the school with existing problems is to always socialize student activities in full-day school policy, provide dispensation for students who have scheduled activities outside of school that has been previously scheduled, conduct weekly evaluations and hold collaboration with institutions that can support full-day school activities in the school.Keywords: Policy Implementation, Full Day School, Elementary SchoolÂ Abstrak: Penelitian ini bertujuan untuk mendeskripsikan 1) implementasi kebijakan full day school yang dilakukan di SDN 3 Blimbing; 2) permasalahan yang dihadapi SDN 3 Blimbing dalam mengimplementasikan full day school; 3) solusi yang dilakukan dalam menyelesaikan permasalahan implementasi kebijakan full day school di SDN 3 Blimbing. Metode penelitian yang dilakukan adalah pendekatan kualitatif dengan jenis penelitian adalah deskriptif. Data diperoleh melalui wawancara, observasi, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa implementasi kebijakan full day school telah dilakukan dilandaskan pada Kebijakan Penguatan Pendidikan Karakter yang dibuat oleh Kementrian Pendidikan Republik Indonesia. Tujuan full day school yang diterapkan di SDN 3 Blimbing Kota Malang adalah supaya siswa-siswa mempunyai karakter yang telah ditetapkan oleh Kementrian Pendidikan Republik Indonesia. Permasalahan yang muncul selama implementasi full day school antra lain sarana dan prasana yang belum memadai, adaptasi guru-guru, karyawan, dan siswa-siswa yang membutuhkan waktu yang relatif lama, kekhawatiran orang tua siswa terhadap anak-anaknya yang duduk di kelas 1 dan 2 dan penyesuaian jadwal sekolah dan kegiatan siswa diluar sekolah yang telah terjadwal sebelumnya. Solusi yang dilakukan oleh pihak sekolah dengan permasalahan yang ada adalah dengan selalu mensosialisakan kegiata-kegiatan siswa dalam kebijakan full day school, memberikan dispensasi terhadap siswa yang ada jadwal kegiatan diluar sekolah yang telah terjadwal sebelumnya, melakukan evaluasi mingguan dan mengadakan kerja sama dengan lembaga yang bisa mendukung kegiatan-kegiatan full day school yang ada di sekolah.Kata kunci: Implementasi Kebijakan, Full Day School, Sekolah Dasar